Malacofauna Report of SEKEM Desert Farm in Bahariya Oasis, Egypt: MALACOFAUNA REPORT FROM BAHARIYA OASIS, EGYPT - Ali, Reham Fathey; Ramdini, Ramdane; El Hawwary , Alaa; Abo Samra, Fatma; Hossam, Dalia; El Hussiny, Buthaina; Helal , Hady Hisham; Abd El Aziz, Taif Hamdy; Abd El Aziz , Nashaat Samy; Mohamed Gouda, Youmna; Mohamed Ghanem, Yossef; Hussien, Ziad Khalil (Annals of Arid Zone, 2024)
This research examines the diversity of malacofauna in reclaimed and un-reclaimed areas of the SEKEM Desert Farm at Bahariya Oasis in the Western Desert of Giza Governorate, Egypt. The farm employs organic farming methods to cultivate crops and medicinal plants. Initially, only three species: Cerastoderma glaucum, Corbicula fluminalis, and Bellamya unicolor were found in the un-reclaimed desert area. However, after reclamation and agricultural development, the species richness of molluscs increased significantly. In the area reclaimed in 2008, 15 molluscs species were identified, while the area reclaimed in 2018/19 harboured 11 species. Most of these species are native to the Nile region, with the exception of two marine-origin species recorded in the nearby Mediterranean regions. The study also identified three species: Eobania vermiculata, Theba pisana, and Xeropicta krynickii that are considered harmful to crops.